PENERAPAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI SISTEM PENCERNAAN PADA MANUSIA - Souwakil, Hadia; Jamdin, Zamrin; Marda, Nurwafiah (Al-Alam: Islamic Science Education Journal, 2024)
This study aims to determine whether the Problem Based Learning (PBL) learning model can improve the cognitive learning outcomes of class VIII students in the material on the human digestive system at MTs. Nurul Ikhlas Ambon, the type of this research was Classroom Action Research conducted in 2 cycles, the subjects of this research were class VIII students of MTs Nurul Ikhlas Ambon, totaling 20 students. The instrument used in this study was a test instrument, with 20 test questions. This research was carried out from November 16, 2022 to December 16, 2022. The results showed that student learning outcomes in the pre-cycle of students who completed 2 students with a completeness percentage of 10 % whereas 18 students did not complete with a completeness percentage of 90%, while in the first cycle stage there were 8 students who completed with a completeness percentage of 40% and did not complete as many as 12 students with a completeness percentage of 60%, while in cycle II students who did not complete as many as 3 students with a completeness percentage of 15% and students who completed as many as 17 students with a completeness percentage of 85%. Thus it can be concluded that the application of the Problem Based Learning (PBL) learning model can improve student learning outcomes.